(untitled) (Educational Dimension, 2021)
The actual problem of linguodidactics is the search for new methods and techniques for working with text based on a text-centric approach to language training. The article identifies and describes the didactic possibilities of using the linguistic-stylistic analysis of texts in the lessons of Russian as a foreign language. The reasons for the need to work with the text as with the highest communicative unit have been determined: 1) works of different styles and genres are used in language lessons as didactic material in the formation of language competence; 2) the tasks of developing speech competence include teaching various types of text analysis; 3) communicative competence is formed on the basis of the text. The goals of using text, including fiction, in Russian language lessons have been identified: 1) linguistic and speech (enrichment of vocabulary, demonstration of the capabilities of the grammatical system; text as a stimulus for discussion); 2) sociocultural (acquaintance with the culture of the country of the target language; “culture described by the language”); 3) ethical and aesthetic (humanistic and aesthetic values; skills of aesthetic perception of fiction). The criteria for selecting a text as an educational material are determined: compliance of the text with educational goals; informativeness; availability; cultural significance; educational orientation; cognitive and ethical-aesthetic value. The effect of the message depends not only on the meaning of the units of the statement, but also on the contextual design, on the idea of the work and the author’s ideas, and on the author’s intentions. Linguistic-stylistic analysis of text, including fiction, is the most important method in teaching Russian as a foreign language: it makes it possible to form students’ conscious attitude to speech activity, develop aesthetic feelings and tastes, master the Russian language and Russian speech in their unity, in functional and stylistic aspect, improve language, speech and communicative competence. Such a study of the Russian language makes it possible to overcome the dryness and cliché in language teaching, to increase its educational capabilities.